Mining Business Licenses in the Perspective of Administrative Law Between State Authority and Community Rights - Damanik, Herlina; Fransisco, Wawan; Wahyudi, Fajar Satriyawan (PT. Hafasy Dwi Nawasena, 2025)
The Mining Business License (IUP) is the main legal instrument in the management of mineral and coal resources in Indonesia. The revision of the Mineral and Mineral Law changes the authority to grant permits from the local government to the central government with the aim of reducing the practice of overlapping permits and corruption and strengthening the effectiveness of supervision. However, this centralization policy poses new challenges in the form of reduced role of local governments, limited community participation, and increased potential for social conflicts with indigenous peoples. This study used the Systematic Literature Review (SLR) method with the PRISMA procedure on 971 articles, until 50 relevant articles were selected for analysis. The results of the study show that the practice of protecting the rights of communities, especially indigenous peoples, is still weak due to the lack of application of the Free, Prior, and Informed Consent (FPIC) principle. In addition, maladministrative practices, weak law enforcement, and lack of transparency worsen the governance of the mining sector and ignore the principle of intergenerational justice. This study confirms the existence of research gaps related to the effectiveness of authority centralization, community-based supervision models, FPIC implementation, and systematic studies of intergenerational justice in mining licensing. These findings contribute to strengthening the legal analysis of mining administration and open up opportunities for regulatory reform towards fairer, accountable, and more sustainable governance.